Effects of home confinement due to COVID-19 pandemic on eccentric hamstring muscle strength in football players - Moreno-Pérez, V.; Del Coso, J.; Romero-Rodriguez, D.; Marcé-Hernández, L.; Peñaranda, M.; Madruga-Parera, M. (Scandinavian Journal of Medicine & Science in Sports, 2020)
At the beginning of March 2020, the World Health Organization declared the coronavirus disease (COVID-19), an infection produced by the virus SARS-CoV-2, a global pandemic. COVID-19 causes an acute respiratory syndrome that can produce severe life-threatening complications in a relatively high proportion of infected individuals.1 The virus that causes COVID-19 spreads mainly from person to person through respiratory droplets, so governments of most countries have declared confinement measures to reduce the propagation. Although the degree of confinement differs among countries, it has often entailed staying at home for several weeks to months. Home isolation has negatively affected all layers of society and has had potentially severe impact on athletes because training and competition in indoor and outdoor sport facilities were suspended. Athletes have been using multiple forms of training to mitigate the detraining effect of confinement on physical conditioning. However, the success of these routines may differ depending on the sports discipline.